India's master plan for groundwater recharge: an assessment and some suggestions for revision - Shah, Tushaar (2008)
The government's Groundwater Recharge Master Plan reflects belated recognition of the growing criticality of groundwater for the Indian economy. The plan aims to raise post-monsoon groundwater levels to three metres below ground level through annual "managed artificial recharge? of 36.4 km3 by constructing some four million spreading-type recharge structures at a cost of Rs 25,000 crore. While this is a step in the right direction, the revised master plan under preparation needs to incorporate socio-economic, institutional and administrative parameters that underpin the implementation of any major change intervention. This paper provides an assessment of the existing plan and offers suggestions for revision.